Proposal and surrogate-based cost-optimal design of an innovative green ammonia and electricity co-production system via liquid air energy storage. (15th May 2022) - Qi, Meng; Kim, Minsu; Dat Vo, Nguyen; Yin, Liang; Liu, Yi; Park, Jinwoo; Moon, Il
Graphical abstract: Highlights: Proposal of an ammonia and electricity co-production system via liquid air energy storage. Systems design and thermal integration lead to the highest energy efficiency of 83%. Formulation of system scheduling model to study the impacts of storage sizing and power allocation. ANN-surrogate-based optimization to establish an economically optimal design. Cost of green ammonia from the co-production system can be lowered to ∼360 €/tonne. Abstract: Green ammonia produced via the Power-to-Ammonia (PtA) process has the great potential to decarbonize the energy supply. The current challenge of green ammonia is the unacceptable cost compared to that produced from fossil energy, which arises owing to the low energy efficiency caused by fluctuations in renewable power and high investment costs. This study aims to tackle these issues by integrating liquid air energy storage (LAES) with the PtA process to manage uncertainties from both sides of power supply and demand, thus forming an innovative ammonia and electricity co-production system to supply power flexibly at peak hours and ensure ammonia production at a constant load. The continuous PtA process enables the use of high-temperature electrolysis, and system thermal integration results in the highest production efficiency of 83%. Flexible operation is achieved by adsorbing dispatchable electricity from the grid and outputting peak electricity for power load shifting, therefore, cost reduction can be achieved via electricity arbitrage. A system scheduling model is formulated to understand the impacts of storage sizing and power allocation on the renewables penetration, grid power output ratio, and the cost of ammonia production. An artificial neural network-based surrogate optimization was performed to establish a cost-optimal design. Investigation at the location of Kramer Junction revealed that the cost of ammonia production can be lowered to 360.74 €/tonne based on a system renewables penetration of 77.6% and grid power output ratio of 43.9%. Moreover, the cost could be further reduced by using an external thermal energy coupled LAES in areas with high electricity prices. These findings clearly demonstrate that the proposed co-production system is an economically viable option for short-term electricity and long-term ammonia hybrid energy storage.